Psychological aspect use of interactive learning technologies of students in the organization of project activities in the conditions of distance education (Actual Problems of Psychology in Educational Institutions, 2023)
The article reveals the peculiarities of using technologies forinteractive learning of students in the organization of project activities.The role and place of the project method in the conditions of distanceeducation is analyzed. Examples of interactive technologies from thepositive experience of their implementation in project activities are offered.The psychological content of the use of interactive technologies in theteacher’s project activity in the lesson is revealed. Emphasis is placed onthe psychological features of the use of interactive learning technologies inthe format of subject-subject interaction between teachers and students ina distance learning format. The pros and cons of using interactive learningtechnologies in organizing project activities are outlined.
Keywords: technologies, project, project activity, distance education, interactive technologies